2018
DOI: 10.1016/j.jpha.2017.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Anti-diabetic activity of quercetin extracted from Phyllanthus emblica L. fruit: In silico and in vivo approaches

Abstract: In this study, molecular interactions of the ligands, quercetin, gallic acid, and metformin with various diabetes mellitus-related protein targets, such as glycogen phosphorylase and peroxisome proliferator-activated receptor gamma, were assessed. It was revealed that quercetin possesses good binding affinity to both targets. Quercetin is a major constituent of methanolic extracts of Phyllanthus emblica fruit. The antihyperglycemic effect of quercetin in streptozotocin (STZ)-induced diabetic rats was examined.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
64
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(66 citation statements)
references
References 24 publications
2
64
0
Order By: Relevance
“…Comparison of the 1 H and 13 C NMR data for fractions A and B revealed that these compounds are quercetin and kaempferol, respectively (Figure ) (Ibrahim, Amin, Ibrahim, Abdelzaher, & Abdelrahman, ). Interestingly, previous studies have demonstrated the antidiabetic activity of quercetin (Abdelkarem & Fadda, ; Srinivasan, Vijayakumar, Kothandaraman, & Palani, ; Yang & Kang, ) and kaempferol (Alkhalidy et al, ; Chandramohan, Al‐Numair, Alsaif, & Veeramani, ; Zang, Zhang, Igarashi, & Yu, ) in different models. The reduction in blood glucose shows that these compounds contribute to the blood glucose lowering activity of methanolic leaf extract of B. pinnatum .…”
Section: Resultsmentioning
confidence: 99%
“…Comparison of the 1 H and 13 C NMR data for fractions A and B revealed that these compounds are quercetin and kaempferol, respectively (Figure ) (Ibrahim, Amin, Ibrahim, Abdelzaher, & Abdelrahman, ). Interestingly, previous studies have demonstrated the antidiabetic activity of quercetin (Abdelkarem & Fadda, ; Srinivasan, Vijayakumar, Kothandaraman, & Palani, ; Yang & Kang, ) and kaempferol (Alkhalidy et al, ; Chandramohan, Al‐Numair, Alsaif, & Veeramani, ; Zang, Zhang, Igarashi, & Yu, ) in different models. The reduction in blood glucose shows that these compounds contribute to the blood glucose lowering activity of methanolic leaf extract of B. pinnatum .…”
Section: Resultsmentioning
confidence: 99%
“…However, in previous reports, quercetin may reduce the risk of T2DM; by inhibition of glycogen phosphorylase which inhibited glycogenolysis, reduced hepatic glucose production [32,33]. Quercetin and rutin reduced glucose absorption from small intestine by inhibition of αamylase and αglucosidases to lowering the blood glucose level [34][35][36]. Coumarin showed antidiabetic activity by stimulating the insulin production from β-cell in pancreas by regulating the glycolysis and inhibition of gluconeogenesis [37].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies also demonstrated antidiabetic properties of QC through a variety of mechanisms. [42][43][44] On the other hand, the relationship between prolonged hyperglycemia and cognitive impairment has been reported. 45 Therefore, part of the memory restoration that is found in diabetic rats could be due to the potency of QC to decrease hyperglycemia and improve other diabetic-related parameters such as dyslipidemia.…”
Section: Discussionmentioning
confidence: 99%